CGMP-dependent protein kinase-2 regulates bone mass and prevents diabetic bone loss. Issue 3 (September 2018) - Ramdani, Ghania; Schall, Nadine; Kalyanaraman, Hema; Wahwah, Nisreen; Moheize, Sahar; Lee, Jenna J; Sah, Robert L; Pfeifer, Alexander; Casteel, Darren E; Pilz, Renate B
Abstract : NO/cGMP signaling is important for bone remodeling in response to mechanical and hormonal stimuli, but the downstream mediator(s) regulating skeletal homeostasis are incompletely defined. We generated transgenic mice expressing a partly-activated, mutant cGMP-dependent protein kinase type 2 (PKG2 R242Q ) under control of the osteoblast-specific Col1a1 promoter to characterize the role of PKG2 in post-natal bone formation. Primary osteoblasts from these mice showed a two- to three-fold increase in basal and total PKG2 activity; they proliferated faster and were resistant to apoptosis compared to cells from WT mice. Male Col1a1- Prkg2 R242Q transgenic mice had increased osteoblast numbers, bone formation rates and Wnt/β-catenin-related gene expression in bone and a higher trabecular bone mass compared to their WT littermates. Streptozotocin-induced type 1 diabetes suppressed bone formation and caused rapid bone loss in WT mice, but male transgenic mice were protected from these effects. Surprisingly, we found no significant difference in bone micro-architecture or Wnt/β-catenin-related gene expression between female WT and transgenic mice; female mice of both genotypes showed higher systemic and osteoblastic NO/cGMP generation compared to their male counterparts, and a higher level of endogenous PKG2 activity may be responsible for masking effects of the PKG2 R242Q transgene in females. Our data support sexual dimorphism in Wnt/β-catenin signaling and PKG2 regulation of this crucial pathway in bone homeostasis. This work establishes PKG2 as a key regulator of osteoblast proliferation and post-natal bone formation.